2007
DOI: 10.1038/ismej.2007.83
|View full text |Cite
|
Sign up to set email alerts
|

Primary producing prokaryotic communities of brine, interface and seawater above the halocline of deep anoxic lake L'Atalante, Eastern Mediterranean Sea

Abstract: Meso-and bathypelagic ecosystems represent the most common marine ecological niche on Earth and contain complex communities of microorganisms that are for the most part ecophysiologically poorly characterized. Gradients of physico-chemical factors (for example, depth-related gradients of light, temperature, salinity, nutrients and pressure) constitute major forces shaping ecosystems at activity 'hot spots' on the ocean floor, such as hydrothermal vents, cold seepages and mud volcanoes and hypersaline lakes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 57 publications
9
129
0
Order By: Relevance
“…Before cDNA synthesis, RNA-containing extracts were purified from DNA by incubation with DNAse I (DNA-free-Kit, Ambion, Austin, TX, USA) at 37 1C for 30 min and the RNA concentrations determined using a NanoDrop ND 1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA). Each RNA sample was immediately converted into cDNA with SuperScript II Reverse Transcriptase (Invitrogen, Carlsbad, CA, USA) and random primers as described elsewhere (Yakimov et al, 2007). The reaction was carried out in a MasterCycler 5331 Gradient (Eppendorf, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before cDNA synthesis, RNA-containing extracts were purified from DNA by incubation with DNAse I (DNA-free-Kit, Ambion, Austin, TX, USA) at 37 1C for 30 min and the RNA concentrations determined using a NanoDrop ND 1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA). Each RNA sample was immediately converted into cDNA with SuperScript II Reverse Transcriptase (Invitrogen, Carlsbad, CA, USA) and random primers as described elsewhere (Yakimov et al, 2007). The reaction was carried out in a MasterCycler 5331 Gradient (Eppendorf, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was performed using DNA templates originating from all depths sampled in triplicates along with a 'no template control'. Mixtures for Q-PCRs and the reaction conditions were as previously described (Yakimov et al, 2007). Q-PCR amplification was analyzed using an automatic setting of the baseline and threshold values.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Discovery, L'Atalante, Urania, Thetis and Bannock basins revealed that DHAB interfaces harbor abundant and diverse microbial communities that include numerous novel candidate divisions that are more productive than most pelagic marine systems (see, for example, Sass et al, 2001;Van Der Wielen et al, 2005;Yakimov et al, 2007;Edgcomb et al, 2009;Stock et al, 2012). Functional analyses of these communities based on PCR amplification of key functional genes as well as activity measurements revealed sulfur cycling and methanogenesis to be dominant prokaryotic metabolic processes supporting life in DHABs and contributing to observed elevated biomass in DHAB haloclines (Daffonchio et al, 2006;Yakimov et al, 2007;Borin et al, 2009). Recent advances in RNA isolation, amplification and high-throughput sequencing make it possible to acquire millions of sequences of transcribed genes from microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sea hypersaline anoxic basins (DHABs) of the Eastern Mediterranean are extreme environments characterized by high salinity and corresponding density, high hydrostatic pressure, absence of light, anoxia, and the presence of a sharp chemocline between brines and the above seawater. Moreover, DHABs contain brines with different composition, and hence each of them constitutes an independent environment, which hosts a peculiar and stratified prokaryotic community, highly adapted to the extreme geosetting (Van der Wielen et al 2005;Daffonchio et al,2006;Yakimov et al 2007). These habitats resulted, therefore, in the selection of unusual microorganisms with peculiar enzyme endowment, i.e.…”
Section: Introductionmentioning
confidence: 99%